Analisis Alur Proses Klaim Bpjs Terhadap Pelayanan Pasien Rawat Inap di Santosa Hospital Bandung Central - Sani Fitriyani; Asti Juniar Lestari (Jurnal Infokes, 2026)
This study aims to analyze the claim process flow of the National Health Insurance (BPJS Health) for inpatient services. The research employed a quantitative descriptive observational method. Data were obtained from the recapitulation of inpatient claim statuses during the period of January to March, and analyzed based on the percentage of claim statuses. The results showed that the percentage of pending claims in January was 35%, in February 33%, and in March 27%. Meanwhile, the percentage of approved claims in January was 64%, in February 65%, and in March 72%. These findings indicate a decrease in pending claims and an increase in approved claims. It can be concluded that accuracy in the BPJS claim process is crucial and must be prioritized by hospitals to minimize claim errors and improve claim acceptance rates. Thus, the claim process flow for BPJS inpatient services involves interconnected stages, starting from patient data recording, medical services, diagnosis coding, to claim verification.